Host defense against systemic infection with Streptococcus pneumoniae is impaired in E-, P-, and E-/P-selectin-deficient mice. - Munoz, F M (1997)
Endothelial selectins mediate rolling of leukocytes on endothelium, a crucial step for leukocyte firm adhesion and emigration into sites of tissue injury and infection. To characterize the role of the endothelial selectins during bacterial sepsis in vivo, Streptococcus pneumoniae (1-10 x 10(6) colony-forming units) was inoculated intraperitoneally into wild-type mice and mice with E-, P-, or E-/P-selectin deficiencies. Mice were followed 10 d for morbidity, survival, clearance of bacteremia, and leukocyte migration to the peritoneal cavity and organs 48 h after infection. All selectin-deficient mice showed a more pronounced morbidity, a significantly higher mortality associated with persistent bacteremia, and a higher bacterial load when compared with wild-type mice. These differences were most remarkable in the E-selectin-deficient mice, which showed the highest rate of mortality and bacteremia (P </= 0.0001). No significant differences were observed among the groups in the inflammatory response present in the peritoneal cavity, brain, liver, spleen, or kidney at 48 h after inoculation. Extensive hepatic and splenic necrosis and thrombosis were noted in E- and P-selectin-deficient mice. Although the absence of endothelial selectins did not substantially impair leukocyte emigration to sites of infection 48 h after pneumococcal sepsis, it resulted in increased mortality and a higher bacterial load in the bloodstream of selectin-deficient mice. These results demonstrate a definitive phenotypic abnormality in E-selectin-deficient mice, and suggest that E- and P-selectin are important in the host defense against S. pneumoniae infection.